The Influence of Discovery Learning Model on Physics Learning Motivation and Critical Thinking Skills of Senior High School Students - Kadek Kariani; Muhammad Arsyad; Husain Husain (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Physics learning in the 21st century requires students to develop not only conceptual understanding but also motivation and critical thinking skills needed to solve scientific problems. However, teacher-centered learning practices often limit students' opportunities to actively explore and construct knowledge. This study aimed to analyze the effect of the discovery learning model on students' physics learning motivation and critical thinking skills at SMA Negeri 1 Soyo Jaya. This research used a quantitative approach with a randomized pretest-posttest control group design involving 28 eleventh-grade students. Data were collected through observation, motivation questionnaires, critical thinking tests, and documentation. Data analysis was conducted using descriptive statistics and inferential analysis through normality tests, homogeneity tests, and independent sample t-tests. The results showed that the experimental class experienced higher improvement than the control class, with motivation scores increasing from 60.43 to 84.67 and critical thinking scores increasing from 50.25 to 64.25. The hypothesis test obtained a significance value of 0.000 < 0.05, indicating a significant effect of discovery learning. These findings show that discovery learning encourages active involvement, independent exploration, and analytical thinking. Therefore, discovery learning can be an effective instructional model to improve students' motivation and critical thinking skills in physics learning.